(untitled) (Research, Society and Development, 2021)
This study aims to reflect on the emergence of mathematical communication, from an activity entitled "My day, my activities", developed in a hospital class located in Belém and linked to the Department of Education of Pará. , to victims of accidents with a vessel’s engine or motor shafts, causing the abrupt partial or total removal of the scalp. The activity aimed to discuss introductory concepts of time measurements, relating them to daily activities of students in their places of origin and in the hospital environment. The research is characterized as qualitative and the data were analyzed in the light of the participationist perspective of interpersonal communication. Two students, aged 10 and 12, attending the 3rd and 4th years of Elementary School, respectively, participated in the activity. We understand that the dialogic methodology adopted to carry out the activity encouraged the engagement of the participants, enabling the individualization of the mathematical discourse from a participationist approach and legitimizing the communication of students in oral and written modalities. Finally, we emphasize the importance of institutional encouragement and support for the work of teachers, academics and researchers in environments considered unusual for formal schooling, in order to guarantee that the fundamental right of access to education is ensured to children and adolescents in Health treatment.